Shifting to bio-based plastics in Austria: An assessment of options within the bioeconomy under land constraints - Benjamin Fleischmann; Nicolas Roux; Andreas Mayer; Lisa Kaufmann; Melanie Pichler; Christian Lauk (Journal of Cleaner Production, 2026)

Characterisation of a touchscreen-based task for assessing cognitive judgement bias in mice: a new translational tool for affective state disorder drug screening - Laura Lopez-Cruz; Benjamin U. Phillips; Lisa M. Saksida; Christopher J. Heath; Timothy J. Bussey (Psychopharmacology, 2026)
Rationale A major obstacle in the pre-clinical study of mood-related disorders and novel affective state therapeutic evaluation is the lack of animal models that fully recapitulate human symptomatology. Objective In this study, we developed a touchscreen-based cognitive judgement bias (CJB) task for mice. Methods In the CJB task, animals first learned to discriminate between two visual stimuli displayed on the touchscreen: one associated with a reward (S+) and one associated with a time-out and flashing house light (S-). Once mice learned to respond to the S + and to withhold responding to the S- consistently, a set of four ambiguous stimuli ranging in visual similarity to the S + and S- stimuli were randomly interspersed in the stimulus presentation sequence. Responses to these ambiguous stimuli were interpreted as a greater expectation of positive (‘optimistic bias’) or negative (‘pessimistic bias’) outcomes as a function of their similarity to the S + or S- stimuli. Results The acute administration of the SSRIs fluoxetine and citalopram, and the 5HT-2 C receptor antagonist SB 242084, did not produce any effects on CJB task performance. However, the noradrenaline/dopamine reuptake inhibitor, bupropion, increased responses to the ambiguous stimuli consistent with the induction of an ‘optimistic bias’, and the pro-depressant tetrabenazine yielded the opposite effect. Conclusion This study underscores the capacity of mice to respond to visually ambiguous stimuli in an ambiguity-dependent manner, a phenomenon observed across various species, including humans. Furthermore, it establishes and validates an operant behavioural task to assess CJB in mice delivered using the touchscreen platform, which has significant cross-species translational potential.

Diet composition of data‐limited marlins ( Istiophoridae ) in the Northwest Atlantic - Joseph J. Dello Russo; John M. Logan; Riley Austin; Zachary T. Whitener; Isabelle Sée; Benjamin M. Hurley; Lisa A. Kerr; Joseph M. Quattro; Walter J. Golet (Journal of Fish Biology, 2026)
Knowledge of the dietary composition of Atlantic marlins, especially for recently acknowledged species such as roundscale spearfish ( Tetrapturus georgii ), is limited, as sample access is constrained by international quotas and intermittent landing rates. A series of annual offshore recreational fishing tournaments target Atlantic blue marlin ( Makaira nigricans ), white marlin ( Kajikia albida ) and roundscale spearfish on their seasonal foraging grounds in the South and Mid‐Atlantic Bight. Through this network of tournaments and recreational anglers, we collected stomachs from Atlantic blue marlin ( n = 32), white marlin ( n = 35) and roundscale spearfish ( n = 44) from 2018 to 2020 to investigate general diet composition. Stomach content analysis and DNA barcoding identified a total of 16 prey families across the three focal species, but the majority of prey weight (%W) was from two families (Scombridae and Ommastrephidae). Blue marlin and roundscale spearfish were predominantly piscivorous (99.0 and 80.6%W fishes, respectively), whereas white marlin mainly consumed cephalopods (80%W). The contribution of Scombridae was highest for blue marlin (94.6%W), intermediate for roundscale spearfish (51.7%W) and lowest for white marlin (11%W), with an inverse pattern of relative contribution for Ommastrephidae (0.9, 16.1 and 73.9%W, respectively). Roundscale spearfish and white marlin, despite having a near identical morphology, had diets composed of different prey types in our sample. These dietary data, from three epipelagic apex predators, provide important information for wider ecosystem‐based studies, including in relation to the Mackerel, Squid and Butterfish Fishery Management Plan overseen by the Mid‐Atlantic Fishery Management Council.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

CSF elevated Tau and P-Tau and normal Aβ42 mainly corresponds to Alzheimer’s disease with dementia with Lewy bodies - Olivier Bousiges; Benjamin Cretin; Lisa Battista; Caroline Schaeffer-Agalède; Nathalie Philippi; Lola Hamied; Alix Ravier; Catherine Demuynck; Candice Muller; Frédéric Blanc (GeroScience, 2026)

Forest Heterogeneity by Chain Saw: How Between‐Patch Variation in Old Growth Attributes Changes the Metacommunities of Beetles - Oliver Mitesser; Marc W. Cadotte; Akira S. Mori; Fons van der Plas; Anne Chao; Julia Rothacher; Claus Bässler; Mirjana Bevanda; Peter H. W. Biedermann; Pia Bradler; Antonio Castañeda‐Gómez; Orsi Decker; et al. (Ecology Letters, 2026)
Metacommunity theory has expanded our understanding of how spatial dynamics and local interactions influence species communities. Different assembly archetypes, reflecting different roles of species differences, habitat differences, and dispersal have been described, but we lack empirical studies specifically in terrestrial habitats testing which archetype is most important. In a replicated design, we experimentally enhanced structural between‐patch heterogeneity in homogeneous production forests and developed a statistical framework controlling for sample incompleteness to detect different metacommunity processes. Meta‐analyses on > 100 K individuals of > 1.3 K beetle species showed an increase of ~60 species in heterogenized forests at γ‐level promoted by increasing α‐diversity consistent with the mass‐effect and an increase of β‐diversity by ~10% supporting species‐sorting . Additionally, we tested β‐deviations from random assembly as a proxy of neutral processes . Findings indicate that enhancing structural heterogeneity can shift forests from patch‐dynamics dominance towards mass‐effect and species‐sorting , offering a promising pathway to restore biodiversity in managed landscapes.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Nature-based Solutions in the Mediterranean Region: A look back and moving forward - Lisa Ernoul; Benjamin Hetherington (Journal for Nature Conservation, 2026)

High-resolution monitoring of Salish Sea estuarine communities through participatory science - Benjamin G. Rubinoff; Emily W. Grason; P. Sean McDonald; Lisa Watkins (Frontiers in Marine Science, 2025)
Agents of global change, such as climate disruptions, habitat loss, and biological invasions, affect nearshore and intertidal ecological communities in acute and chronic ways. Biological monitoring aims to track the changes in ecological communities over time, yet temporal mismatches between sampling regimes, environmental stressors, and corresponding ecological responses of interest often limit the utility of monitoring data for testing hypotheses related to these changes. Participatory science, alternatively “citizen science”, can increase the geographic and temporal scale of monitoring and can be a tool to address this limitation. By improving statistical power through higher resolution and a larger scale of data, participatory science programs can detect how global change alters highly dynamic ecological communities. In this study, we evaluate insights from a participatory science dataset (Washington Sea Grant Crab Team) on nearshore mobile epifaunal communities in the Salish Sea, how they differ across habitat types and over time and how they responded to an atmospheric heatwave. Nearshore communities varied across channel, lagoon, and tideflat habitat types, with community metrics and species identities aligning with the environmental characteristics of each habitat type. Though these communities experience high seasonal variability, habitat type differences were consistent over the seven years of data collected. While some sites did experience extreme excursions of water temperature as a result of the 2021 atmospheric heatwave, neither short- nor long-term impacts were detected in the ecological communities monitored at the regional scale. Two factors are likely important in this conclusion: 1. We monitored mobile epifauna, which may be able to migrate to mitigate extreme events and 2. Water temperatures during the heatwave rarely exceeded those experienced at the sites during other times of year. The seasonal variability of the ecological communities observed in these dynamic environments suggests avoiding snapshot sampling in favor of an approach that offers high temporal resolution, as some participatory science programs can, to be able to accurately disentangle effects of acute stressors from the noise of natural variability.

A practical framework to evaluate the feasibility of incentive-based approaches to reduce bycatch of marine mammals and other protected species - Manuel Bellanger; Benjamin Dudouet; Sophie Gourguet; Olivier Thébaud; Lisa T. Ballance; Nicolas Becu; Kathryn D. Bisack; Annie Cudennec; Fabienne Daurès; Sigrid Lehuta; Rebecca Lent; C. Tara Marshall; et al. (Marine Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Leaf architecture and functional traits for 122 species at the University of California Botanical Garden at Berkeley - Ilaine Silveira Matos; Mickey Boakye; Monica Antonio; Sonoma Carlos; Ashley Chu; Miguel A. Duarte; Andrea Echevarria; Adrian Fontao; Lisa Garcia; LeeAnn Huang; Breanna Carrillo Johnson; Shama Joshi; et al. (Ecology, 2024)
The dataset contains leaf venation architecture and functional traits for a phylogenetically diverse set of 122 plant species (including ferns, basal angiosperms, monocots, basal eudicots, asterids, and rosids) collected from the living collections of the University of California Botanical Garden at Berkeley (37.87° N, 122.23° W; CA, USA) from February to September 2021. The sampled species originated from all continents, except Antarctica, and are distributed in different growth forms (aquatic, herb, climbing, tree, shrub). The functional dataset comprises 31 traits (mechanical, hydraulic, anatomical, physiological, economical, and chemical) and describes six main leaf functional axes (hydraulic conductance, resistance and resilience to damages caused by drought and herbivory, mechanical support, and construction cost). It also describes how architecture features vary across venation networks. Our trait dataset is suitable for (1) functional and architectural characterization of plant species; (2) identification of venation architecture‐function trade‐offs; (3) investigation of evolutionary trends in leaf venation networks; and (4) mechanistic modeling of leaf function. Data are made available under the Open Data Commons Attribution License.

Mutant PTPMT1 disrupts cardiolipin metabolism and mitochondrial bioenergetics leading to a neurodevelopmental syndrome - Micol Falabella; Chiara Pizzamiglio; Luis Carlos Tabara; Benjamin Munro; Mohamed S. Abdel-Hamid; Ece Sonmezler; William L. Macken; Shanti Lu; Lisa Tilokani; Padraig J. Flannery; Simon A.S. Pope; Simon J.R. Heales; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Conceptualising rural environmental justice in Europe in an age of climate-influenced landscape transformations - David Brown; Benjamin Bégou; Floriane Clement; Brendan Coolsaet; Lisa Darmet; Mathilde Gingembre; Zuzana V. Harmáčková; Adrian Martin; Barbora Nohlová; Cécile Barnaud (Journal of Rural Studies, 2024)

Spatial distribution, bioaccessibility, and human health implications of potentially toxic elements in mining-impacted topsoils in Obuasi Municipality of Ghana - Benjamin Darko Asamoah; Lily Lisa Yevugah; Lawrence Sheringham Borquaye; Matt Dodd; Godfred Darko (Environmental Geochemistry and Health, 2024)

Downslope variability in deep-water slope channel fill facies and stacking patterns - Benjamin G. Daniels; Stephen M. Hubbard; Lisa Stright; Brian W. Romans (Marine and Petroleum Geology, 2024)

Recommendations for quantitative uncertainty consideration in ecology and evolution - Emily G. Simmonds; Kwaku P. Adjei; Benjamin Cretois; Lisa Dickel; Ricardo González-Gil; Jack H. Laverick; Caitlin P. Mandeville; Elizabeth G. Mandeville; Otso Ovaskainen; Jorge Sicacha-Parada; Emma S. Skarstein; Bob O'Hara (Trends in Ecology & Evolution, 2024)

Systematic CFD-based evaluation of physical factors influencing the spatiotemporal distribution patterns of microplastic particles in lakes - Pouyan Ahmadi; Franz Dichgans; Lisa Jagau; Christian Schmidt; Vadym Aizinger; Benjamin S. Gilfedder; Jan H. Fleckenstein (Science of The Total Environment, 2024)

Status of intertidal populations of Pismo clams (Tivela stultorum) across their range in California - Alexandria R. Marquardt; Sara K. Park; Eliana G. Maietta; Noël M. Clark; Grant T. Waltz; Lisa A. Needles; Benjamin I. Ruttenberg (Regional Studies in Marine Science, 2023)

Distribution and in-vitro bioaccessibility of potentially toxic metals in surface soils from a mining and a non-mining community in Ghana: implications for human health - Benjamin Darko Asamoah; Matt Dodd; Lily Lisa Yevugah; Lawrence Sheringham Borquaye; Alexander Boateng; Marian Asantewah Nkansah; Godfred Darko (Environmental Geochemistry and Health, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Bioaccumulated provitamin A in black soldier fly larvae is bioavailable and capable of improving vitamin A status of gerbils - Lisa Morand-Laffargue; Stéphane Delbecq; Benjamin Creton; Damien Sabatier; Marie Papin; Claudie Dhuique-Mayer; Patrick Borel (Food Research International, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Relationships between soil and badger elemental concentrations across a heterogeneously contaminated landscape - Andrea Sartorius; Molly Cahoon; Davide Corbetta; Llorenç Grau-Roma; Matthew F. Johnson; Elsa Sandoval Barron; Matthew Smallman-Raynor; Benjamin M.C. Swift; Lisa Yon; Scott Young; Malcolm Bennett (Science of The Total Environment, 2023)

Climate variability and simultaneous breadbasket yield shocks as observed in long-term yield records - Weston Anderson; Walter Baethgen; Fabian Capitanio; Philippe Ciais; Benjamin I. Cook; Cunha G.R. da Cunha; Lisa Goddard; Bernhard Schauberger; Kai Sonder; Guillermo Podestá; Marijn van der Velde; Liangzhi You (Agricultural and Forest Meteorology, 2023)

Intergenerational Interventions to Cultivate DEI-Champions: Increased Resilience and Accountability Through “Shipboard” Experiences - Raquel Bryant; Benjamin Keisling; Brian Starks; Bella Nunn; Lisa White; Jonathan Lewis; Sharon Cooper (Oceanography, 2023)
We developed All-ABOARD (Alliance Building Offshore to Achieve Resilience and Diversity) to meet the ever-increasing needs of cultivating a diverse geoscience workforce. All-ABOARD incorporates the Be the Messenger theoretical framework in all programmatic aspects to encourage participants to think about their own identities, positionalities, and privileges. Drawing from US-based institutions, we recruited four teams of four to five members who spanned a spectrum of positionality and career stages. To evaluate the efficacy of the program, we collected both quantitative and qualitative data at different intervals to measure changes in participants’ understanding and perception of identity, culture, respect, and diversity. The year-long core programming included regular webinars via Zoom and an in-person retreat. We found that immersive experiences and intergenerational teams led to the cultivation of a strong identity as a DEI-champion, enhanced group cohesion, and promoted feelings of resilience among participants. Our participants reported they felt most accountable to themselves and their teams, and that learning was accelerated by bringing together teams from multiple institutions to collaborate across intergenerational boundaries. Our program provides a model for training DEI-champions in geoscience who can advance strategic objectives in their home environments and demonstrates how frameworks from the social sciences can be effectively leveraged to transform geoscience.

The Remarkable Innate Resistance of Burkholderia bacteria to Cationic Antimicrobial Peptides: Insights into the Mechanism of AMP Resistance - Jenisha Ghimire; Shantanu Guha; Benjamin J. Nelson; Lisa A. Morici; William C. Wimley (The Journal of Membrane Biology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Malignancy risk in individuals with familial adenomatous polyposis receiving biologics and immunomodulators - Muhammad Salman Faisal; Carol A. Burke; Jean-Paul Achkar; Benjamin Click; Margaret O’Malley; Lisa LaGuardia; Susan Milicia; Brandie Leach; David Liska; James Church; Matthew Kalady; Gautam Mankaney (Familial Cancer, 2022)

Post-VX exposure treatment of rats with engineered phosphotriesterases - Lisa Stigler; Anja Köhler; Marianne Koller; Laura Job; Benjamin Escher; Heidrun Potschka; Horst Thiermann; Arne Skerra; Franz Worek; Timo Wille (Archives of Toxicology, 2022)
The biologically stable and highly toxic organophosphorus nerve agent (OP) VX poses a major health threat. Standard medical therapy, consisting of reactivators and competitive muscarinic receptor antagonists, is insufficient. Recently, two engineered mutants of the Brevundimonas diminuta phosphotriesterase (PTE) with enhanced catalytic efficiency ( k cat / K M = 21 to 38 × 10 6 M −1 min −1 ) towards VX and a preferential hydrolysis of the more toxic P(−) enantiomer were described: PTE-C23(R152E)-PAS(100)-10-2-C3(I106A/C59V/C227V/E71K)-PAS(200) (PTE-2), a single-chain bispecific enzyme with a PAS linker and tag having enlarged substrate spectrum, and 10-2-C3(C59V/C227V)-PAS(200) (PTE-3), a stabilized homodimeric enzyme with a double PASylation tag (PAS-tag) to reduce plasma clearance. To assess in vivo efficacy, these engineered enzymes were tested in an anesthetized rat model post-VX exposure (~ 2LD 50 ) in comparison with the recombinant wild-type PTE (PTE-1), dosed at 1.0 mg kg −1 i.v.: PTE-2 dosed at 1.3 mg kg −1 i.v. (PTE-2.1) and 2.6 mg kg −1 i.v. (PTE-2.2) and PTE-3 at 1.4 mg kg −1 i.v. Injection of the mutants PTE-2.2 and PTE-3, 5 min after s.c. VX exposure, ensured survival and prevented severe signs of a cholinergic crisis. Inhibition of erythrocyte acetylcholinesterase (AChE) could not be prevented. However, medulla oblongata and diaphragm AChE activity was partially preserved. All animals treated with the wild-type enzyme, PTE-1, showed severe cholinergic signs and died during the observation period of 180 min. PTE-2.1 resulted in the survival of all animals, yet accompanied by severe signs of OP poisoning. This study demonstrates for the first time efficient detoxification in vivo achieved with low doses of heterodimeric PTE-2 as well as PTE-3 and indicates the suitability of these engineered enzymes for the development of highly effective catalytic scavengers directed against VX.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Inactive rhomboid proteins RHBDF1 and RHBDF2 (iRhoms): a decade of research in murine models - Lisa M. Burzenski; Benjamin E. Low; Vivek Kohar; Leonard D. Shultz; Michael V. Wiles; Vishnu Hosur (Mammalian Genome, 2021)
Rhomboid proteases, first discovered in Drosophila , are intramembrane serine proteases. Members of the rhomboid protein family that are catalytically deficient are known as inactive rhomboids (iRhoms). iRhoms have been implicated in wound healing, cancer, and neurological disorders such as Alzheimer’s and Parkinson’s diseases, inflammation, and skin diseases. The past decade of mouse research has shed new light on two key protein domains of iRhoms—the cytosolic N-terminal domain and the transmembrane dormant peptidase domain—suggesting new ways to target multiple intracellular signaling pathways. This review focuses on recent advances in uncovering the unique functions of iRhom protein domains in normal growth and development, growth factor signaling, and inflammation, with a perspective on future therapeutic opportunities.

KP772 overcomes multiple drug resistance in malignant lymphoma and leukemia cells in vitro by inducing Bcl-2-independent apoptosis and upregulation of Harakiri - Lisa Kater; Benjamin Kater; Michael A. Jakupec; Bernhard K. Keppler; Aram Prokop (JBIC Journal of Biological Inorganic Chemistry, 2021)
Despite high cure rates in pediatric patients with acute leukemia, development of resistance limits the efficacy of antileukemic therapy. Tris (1,10-phenanthroline) tris (thiocyanato-κ N )lanthanum(III) (KP772) is an experimental antineoplastic agent to which multidrug-resistant cell models have shown hypersensitivity. Antiproliferative and apoptotic activities of KP772 were tested in leukemia, lymphoma and solid tumor cell lines as well as primary leukemia cells (isolated from the bone marrow of a child with acute myeloid leukemia (AML). The ability to overcome drug resistances was investigated in doxorubicin- and vincristine-resistant cell lines. Real-time PCR was used to gain insight into the mechanism of apoptosis induction. KP772 inhibited proliferation and induced apoptosis in various leukemia and lymphoma cell lines in a concentration-dependent manner (LC 50 = 1–2.5 µM). Primary AML cells were also sensitive to KP772, whereas daunorubicin showed no significant effect. KP772 induces apoptosis independently of Bcl-2, Smac, and the CD95 receptor and is also effective in caspase 3-deficient MCF7 cells, indicating that apoptosis is partly triggered independently of caspase 3. mRNA expression profiling revealed an upregulation of the BH3-only Bcl-2 protein Harakiri in the course of KP772-induced apoptosis. Remarkably, KP772 overcame drug resistance to doxorubicin and vincristine in vitro, and the apoptotic effect in resistant cells was even superior to that in non-resistant parental cells. In combination with vincristine, doxorubicin and cytarabine, synergistic effects were observed in BJAB cells. The cytotoxic potency in vitro/ex vivo and the remarkable ability to overcome multidrug resistance propose KP772 as a promising candidate drug for antileukemic therapy, especially of drug-refractory malignancies. Graphic abstract

Leaf manganese concentrations as a tool to assess belowground plant functioning in phosphorus-impoverished environments - Hans Lambers; Ian J. Wright; Caio Guilherme Pereira; Peter J. Bellingham; Lisa Patrick Bentley; Alex Boonman; Lucas A. Cernusak; William Foulds; Sean M. Gleason; Emma F. Gray; Patrick E. Hayes; Robert M. Kooyman; et al. (Plant and Soil, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Horizontal and Vertical Movement Patterns and Habitat Use of Juvenile Porbeagles (Lamna nasus) in the Western North Atlantic - Gregory Skomal; Heather Marshall; Benjamin Galuardi; Lisa Natanson; Camrin D. Braun; Diego Bernal (Frontiers in Marine Science, 2021)
The porbeagle (Lamna nasus) is a large, highly migratory endothermic shark broadly distributed in the higher latitudes of the Atlantic, South Pacific, and Indian Oceans. In the North Atlantic, the porbeagle has a long history of fisheries exploitation and current assessments indicate that this stock is severely overfished. Although much is known of the life history of this species, there is little fisheries-independent information about habitat preferences and ecology. To examine migratory routes, vertical behavior, and environmental associations in the western North Atlantic, we deployed pop-up satellite archival transmitting tags on 20 porbeagles in late November, 2006. The sharks, ten males and ten females ranging from 128 to 154 cm fork length, were tagged and released from a commercial longline fishing vessel on the northwestern edge of Georges Bank, about 150 km east of Cape Cod, MA. The tags were programmed to release in March ( n = 7), July ( n = 7), and November ( n = 6) of 2007, and 17 (85%) successfully reported. Based on known and derived geopositions, the porbeagles exhibited broad seasonally-dependent horizontal and vertical movements ranging from minimum linear distances of 937 to 3,310 km and from the surface to 1,300 m, respectively. All of the sharks remained in the western North Atlantic from the Gulf of Maine, the Scotian Shelf, on George's Bank, and in the deep, oceanic waters off the continental shelf along the edge of, and within, the Gulf Stream. In general, the population appears to be shelf-oriented during the summer and early fall with more expansive offshore radiation in the winter and spring. Although sharks moved through temperatures ranging from 2 to 26°C, the bulk of their time (97%) was spent in 6-20°C. In the summer months, most of the sharks were associated with the continental shelf moving between the surface and the bottom and remaining < 200 m deep. In the late fall and winter months, the porbeagles moved into pelagic habitat and exhibited two behavioral patterns linked with the thermal features of the Gulf Stream: “non-divers” ( n = 7) largely remained at epipelagic depths and “divers” ( n = 10) made frequent dives into and remained at mesopelagic depths (200–1000 m). These data demonstrate that juvenile porbeagles are physiologically capable of exploiting the cool temperate waters of the western North Atlantic as well as the mesopelagic depths of the Gulf Stream, possibly allowing exploitation of prey not available to other predators.

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

A New Paradigm for Social License as a Path to Marine Sustainability - Lisa B. Uffman-Kirsch; Benjamin J. Richardson; Elizabeth Ingrid van Putten (Frontiers in Marine Science, 2020)

Determinants of sulphur chemolithoautotrophy in the extremely thermoacidophilic Sulfolobales - Benjamin M. Zeldes; Andrew J. Loder; James A. Counts; Mashkurul Haque; Karl A. Widney; Lisa M. Keller; Sonja‐Verena Albers; Robert M. Kelly (Environmental Microbiology, 2019)
Summary Species in the archaeal order Sulfolobales thrive in hot acid and exhibit remarkable metabolic diversity. Some species are chemolithoautotrophic, obtaining energy through the oxidation of inorganic substrates, sulphur in particular, and acquiring carbon through the 3‐hydroxypropionate/4‐hydroxybutyrate (3‐HP/4‐HB) CO 2 ‐fixation cycle. The current model for sulphur oxidation in the Sulfolobales is based on the biochemical analysis of specific proteins from Acidianus ambivalens , including sulphur oxygenase reductase (SOR) that disproportionates S° into H 2 S and sulphite (SO 3 2− ). Initial studies indicated SOR catalyses the essential first step in oxidation of elemental sulphur, but an ancillary role for SOR as a ‘recycle’ enzyme has also been proposed. Here, heterologous expression of both SOR and membrane‐bound thiosulphate‐quinone oxidoreductase (TQO) from Sulfolobus tokodaii ‘restored’ sulphur oxidation capacity in Sulfolobus acidocaldarius DSM639, but not autotrophy, although earlier reports indicate this strain was once capable of chemolithoautotrophy. Comparative transcriptomic analyses of Acidianus brierleyi , a chemolithoautotrophic sulphur oxidizer, and S. acidocaldarius DSM639 showed that while both share a strong transcriptional response to elemental sulphur, S. acidocaldarius DSM639 failed to upregulate key 3‐HP/4‐HB cycle genes used by A. brierleyi to drive chemolithoautotrophy. Thus, the inability for S. acidocaldarius DSM639 to grow chemolithoautotrophically may be rooted more in gene regulation than the biochemical capacity.

Multi-gene panel testing confirms phenotypic variability in MUTYH-Associated Polyposis - Erin G. Sutcliffe; Amanda Bartenbaker Thompson; Amy R. Stettner; Megan L. Marshall; Maegan E. Roberts; Lisa R. Susswein; Ying Wang; Rachel T. Klein; Kathleen S. Hruska; Benjamin D. Solomon (Familial Cancer, 2019)

Translational tests involving non-reward: methodological considerations - Benjamin U. Phillips; Laura Lopez-Cruz; Lisa M. Saksida; Timothy J. Bussey (Psychopharmacology, 2019)

Management of loss and damage in small island developing states: implications for a 1.5 °C or warmer world - Adelle Thomas; Lisa Benjamin (Regional Environmental Change, 2018)

Modeling marine pelagic fish species spatiotemporal distributions utilizing a maximum entropy approach - Lifei Wang; Lisa A. Kerr; Nicholas R. Record; Eric Bridger; Benjamin Tupper; Katherine E. Mills; Edward M. Armstrong; Andrew J. Pershing (Fisheries Oceanography, 2018)
Understanding how ocean conditions influence fish distributions is critical for elucidating the role of climate in ecosystem change and forecasting how fish may be distributed in the future. Traditional species distribution models are often applied to scientific‐survey data, which include species presence‐absence information, to predict distributions. Maximum entropy (MaxEnt) models are promising tools as they can be applied to presence‐only data (e.g., data collected from fishermen targeting a specific species or from observers in citizen‐science programs). We used MaxEnt models to relate occurrence records of three marine pelagic fish (Atlantic herring, Atlantic mackerel, and butterfish) in fishery‐dependent data to environmental conditions (sea surface temperature ( SST ) and chlorophyll‐ a concentration from satellite remote sensing, bathymetry, and climate indices), and evaluated model performance by both cross‐validation and validation using fishery‐independent data. We developed monthly habitat suitability maps for these fish in the Northwest Atlantic Shelf area, and assessed the relative influence of environmental factors on their distributions. Across months, their suitable habitat areas varied with each species exhibiting inshore‐offshore and north‐south movements in response to changing environmental conditions. Overall, SST and chlorophyll‐ a concentration had the greatest influence on the distributions of these fish, with bathymetry having moderate influence and climate indices having little influence. Our application of MaxEnt models enabled us to integrate presence‐only data and high resolution environmental data from satellite remote sensing to describe spatiotemporal distributions of marine pelagic fish. These models were used to hindcast species occurrence in relation to historical environmental conditions to evaluate their predictive performance, and have the potential to provide nowcasts in relation to current conditions or forecasts of species future distributions.

Effects of temperature and precipitation on grassland bird nesting success as mediated by patch size - Benjamin Zuckerberg; Christine A. Ribic; Lisa A. McCauley (Conservation Biology, 2018)
Grassland birds are declining faster than any other bird guild across North America. Shrinking ranges and population declines are attributed to widespread habitat loss and increasingly fragmented landscapes of agriculture and other land uses that are misaligned with grassland bird conservation. Concurrent with habitat loss and degradation, temperate grasslands have been disproportionally affected by climate change relative to most other terrestrial biomes. Distributions of grassland birds often correlate with gradients in climate, but few researchers have explored the consequences of weather on the demography of grassland birds inhabiting a range of grassland fragments. To do so, we modeled the effects of temperature and precipitation on nesting success rates of 12 grassland bird species inhabiting a range of grassland patches across North America (21,000 nests from 81 individual studies). Higher amounts of precipitation in the preceding year were associated with higher nesting success, but wetter conditions during the active breeding season reduced nesting success. Extremely cold or hot conditions during the early breeding season were associated with lower rates of nesting success. The direct and indirect influence of temperature and precipitation on nesting success was moderated by grassland patch size. The positive effects of precipitation in the preceding year on nesting success were strongest in relatively small grassland patches and had little effect in large patches. Conversely, warm temperatures reduced nesting success in small grassland patches but increased nesting success in large patches. Mechanisms underlying these differences may be patch‐size‐induced variation in microclimates and predator activity. Although the exact cause is unclear, large grassland patches, the most common metric of grassland conservation, appears to moderate the effects of weather on grassland‐bird demography and could be an effective component of climate‐change adaptation.

Selective effects of 5-HT2C receptor modulation on performance of a novel valence-probe visual discrimination task and probabilistic reversal learning in mice - Benjamin U. Phillips; Sigma Dewan; Simon R. O. Nilsson; Trevor W. Robbins; Christopher J. Heath; Lisa M. Saksida; Timothy J. Bussey; Johan Alsiö (Psychopharmacology, 2018)

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Perceptions of climate change risk in The Bahamas - Adelle Thomas; Lisa Benjamin (Journal of Environmental Studies and Sciences, 2018)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Assessing trait‐based scaling theory in tropical forests spanning a broad temperature gradient - Brian J. Enquist; Lisa Patrick Bentley; Alexander Shenkin; Brian Maitner; Van Savage; Sean Michaletz; Benjamin Blonder; Vanessa Buzzard; Tatiana Erika Boza Espinoza; William Farfan‐Rios; Christopher E. Doughty; Gregory R. Goldsmith; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical elevation gradients are natural laboratories to assess how changing climate can influence tropical forests. However, there is a need for theory and integrated data collection to scale from traits to ecosystems. We assess predictions of a novel trait‐based scaling theory, including whether observed shifts in forest traits across a broad tropical temperature gradient are consistent with local phenotypic optima and adaptive compensation for temperature. Location An elevation gradient spanning 3,300 m and consisting of thousands of tropical tree trait measures taken from 16 1‐ha tropical forest plots in southern Perú, where gross and net primary productivity (GPP and NPP) were measured. Time period April to November 2013. Major taxa studied Plants; tropical trees. Methods We developed theory to scale from traits to communities and ecosystems and tested several predictions. We assessed the covariation between climate, traits, biomass and GPP and NPP. We measured multiple traits linked to variation in tree growth and assessed their frequency distributions within and across the elevation gradient. We paired these trait measures across individuals within 16 forests with simultaneous measures of ecosystem net and gross primary productivity. Results Consistent with theory, variation in forest NPP and GPP primarily scaled with forest biomass, but the secondary effect of temperature on productivity was much less than expected. This weak temperature dependence appears to reflect directional shifts in several mean community traits that underlie tree growth with decreases in site temperature. Main conclusions The observed shift in traits of trees that dominate in more cold environments is consistent with an ‘adaptive/acclimatory’ compensation for the kinetic effects of temperature on leaf photosynthesis and tree growth. Forest trait distributions across the gradient showed overly peaked and skewed distributions, consistent with the importance of local filtering of optimal growth traits and recent shifts in species composition and dominance attributable to warming from climate change. Trait‐based scaling theory provides a basis to predict how shifts in climate have and will influence the trait composition and ecosystem functioning of tropical forests.

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Minipig and Human Metabolism of Aldehyde Oxidase Substrates: In Vitro–In Vivo Comparisons - David J. Wilkinson; Rosalind L. Southall; Mingguang Li; Lisa M. Wright; Lindsay J. Corfield; Thomas A. Heeley; Benjamin Bratby; Ranbir Mannu; Sarah L. Johnson; Victoria Shaw; Holly L. Friett; Louise A. Blakeburn; et al. (The AAPS Journal, 2017)

Contextual exclusion processing: an fMRI study of rejection in a performance-related context - Lisa Wagels; Rene Bergs; Benjamin Clemens; Magdalena Bauchmüller; Ruben C. Gur; Frank Schneider; Ute Habel; Nils Kohn (Brain Imaging and Behavior, 2017)

Predicting trait‐environment relationships for venation networks along an Andes‐Amazon elevation gradient - Benjamin Blonder; Norma Salinas; Lisa Patrick Bentley; Alexander Shenkin; Percy O. Chambi Porroa; Yolvi Valdez Tejeira; Cyrille Violle; Nikolaos M. Fyllas; Gregory R. Goldsmith; Roberta E. Martin; Gregory P. Asner; Sandra Díaz; et al. (Ecology, 2017)
Understanding functional trait‐environment relationships ( TER s) may improve predictions of community assembly. However, many empirical TER s have been weak or lacking conceptual foundation. TER s based on leaf venation networks may better link individuals and communities via hydraulic constraints. We report measurements of vein density, vein radius, and leaf thickness for more than 100 dominant species occurring in ten forest communities spanning a 3,300 m Andes‐Amazon elevation gradient in Peru. We use these data to measure the strength of TER s at community scale and to determine whether observed TER s are similar to those predicted by physiological theory. We found strong support for TER s between all traits and temperature, as well weaker support for a predicted TER between maximum abundance‐weighted leaf transpiration rate and maximum potential evapotranspiration. These results provide one approach for developing a more mechanistic trait‐based community assembly theory.

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

Elucidating the spatio‐temporal dynamics of an emerging wildlife pathogen using approximate Bayesian computation - Olivier Rey; Lisa Fourtune; Ivan Paz‐Vinas; Géraldine Loot; Charlotte Veyssière; Benjamin Roche; Simon Blanchet (Molecular Ecology, 2015)
Emerging pathogens constitute a severe threat for human health and biodiversity. Determining the status (native or non‐native) of emerging pathogens, and tracing back their spatio‐temporal dynamics, is crucial to understand the eco‐evolutionary factors promoting their emergence, to control their spread and mitigate their impacts. However, tracing back the spatio‐temporal dynamics of emerging wildlife pathogens is challenging because (i) they are often neglected until they become sufficiently abundant and pose socio‐economical concerns and (ii) their geographical range is often little known. Here, we combined classical population genetics tools and approximate Bayesian computation (i.e. ABC ) to retrace the dynamics of Tracheliastes polycolpus, a poorly documented pathogenic ectoparasite emerging in Western Europe that threatens several freshwater fish species. Our results strongly suggest that populations of T. polycolpus in France emerged from individuals originating from a unique genetic pool that were most likely introduced in the 1920s in central France. From this initial population, three waves of colonization occurred into peripheral watersheds within the next two decades. We further demonstrated that populations remained at low densities, and hence undetectable, during 10 years before a major demographic expansion occurred, and before its official detection in France. These findings corroborate and expand the few historical records available for this emerging pathogen. More generally, our study demonstrates how ABC can be used to determine the status, reconstruct the colonization history and infer key evolutionary parameters of emerging wildlife pathogens with low data availability, and for which samples from the putative native area are inaccessible.

Methane seep ecosystem functions and services from a recently discovered southern California seep - Benjamin M. Grupe; Monika L. Krach; Alexis L. Pasulka; Jillian M. Maloney; Lisa A. Levin; Christina A. Frieder (Marine Ecology, 2015)
The recent discovery of a methane seep with diverse microhabitats and abundant groundfish in the San Diego Trough (1020 m) off the coast of Del Mar, California raised questions about the role of seep ecosystem functions and services in relation to continental margins. We used multicorer and ROV grab samples and an ROV survey to characterize macrofaunal structure, diversity, and trophic patterns in soft sediments and authigenic carbonates; seep microhabitats and taxa observed; and the abundance and spatial patterns of fishery‐relevant species. Biogenic microhabitats near the Del Mar Seep included microbially precipitated carbonate boulders, bacterial mats, vesicomyid clam beds, frenulate and ampharetid beds, vestimentiferan tubeworm clumps, and fields of Bathysiphon filiformis tubes. Macrofaunal abundance increased and mean faunal δ 13 C signatures decreased in multicorer samples nearer the seep, suggesting that chemosynthetic production enhanced animal densities outside the seep center. Polychaetes dominated sediments, and ampharetids became especially abundant near microbial mats, while gastropods, hydroids, and sponges dominated carbonate rocks. A wide range of stable isotopic signatures reflected the diversity of microhabitats, and methane‐derived carbon was the most prevalent source of nutrition for several taxa, especially those associated with carbonates. Megafaunal species living near the seep included longspine thornyhead ( Sebastolobus altivelis ), Pacific dover sole ( Microstomus pacificus ), and lithodid crabs ( Paralomis verrilli ), which represent targets for demersal fisheries. Sebastolobus altivelis was especially abundant (6.5–8.2 fish·100 m −2 ) and appeared to aggregate near the most active seep microhabitats. The Del Mar Methane Seep, like many others along the world's continental margins, exhibits diverse ecosystem functions and enhances regional diversity. Seeps such as this one may also contribute ecosystem services if they provide habitat for fishery species, export production to support margin food webs, and serve as sinks for methane‐derived carbon.

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Preliminary differences in peripheral immune markers and brain metabolites between fatigued and non-fatigued breast cancer survivors: a pilot study - Suzanna Maria Zick; Heather Zwickey; Lisa Wood; Bradley Foerster; Tohfa Khabir; Benjamin Wright; Eric Ichesco; Ananda Sen; Richard Edmund Harris (Brain Imaging and Behavior, 2014)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Variation in hair δ13C and δ15N values in long-tailed macaques (Macaca fascicularis) from Singapore - Michael A. Schillaci; J. Margaret Castellini; Craig A. Stricker; Lisa Jones-Engel; Benjamin P. Y.-H. Lee; Todd M. O’Hara (Primates, 2014)

A 3-dimensional human embryonic stem cell (hESC)-derived model to detect developmental neurotoxicity of nanoparticles - Lisa Hoelting; Benjamin Scheinhardt; Olesja Bondarenko; Stefan Schildknecht; Marion Kapitza; Vivek Tanavde; Betty Tan; Qian Yi Lee; Stefan Mecking; Marcel Leist; Suzanne Kadereit (Archives of Toxicology, 2013)

Amyloid-β(1–42) Protofibrils Formed in Modified Artificial Cerebrospinal Fluid Bind and Activate Microglia - Geeta S. Paranjape; Shana E. Terrill; Lisa K. Gouwens; Benjamin M. Ruck; Michael R. Nichols (Journal of Neuroimmune Pharmacology, 2013)

Breast cancer risk factors differ between Asian and white women with BRCA1/2 mutations - Monique A. de Bruin; Ava Kwong; Benjamin A. Goldstein; Jafi A. Lipson; Debra M. Ikeda; Lisa McPherson; Bhavna Sharma; Ani Kardashian; Elizabeth Schackmann; Kerry E. Kingham; Meredith A. Mills; Dee W. West; et al. (Familial Cancer, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Predicting Capacity Demand on Sanctuaries for African Chimpanzees (Pan troglodytes) - Lisa J. Faust; Doug Cress; Kay H. Farmer; Stephen R. Ross; Benjamin B. Beck (International Journal of Primatology, 2011)

A preliminary investigation of varenicline for heavy drinking smokers - Lisa M. Fucito; Benjamin A. Toll; Ran Wu; Denise M. Romano; Ece Tek; Stephanie S. O’Malley (Psychopharmacology, 2011)

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Venation networks and the origin of the leaf economics spectrum - Benjamin Blonder; Cyrille Violle; Lisa Patrick Bentley; Brian J. Enquist (Ecology Letters, 2011)
Ecology Letters (2011) 14: 91–100 Abstract The leaf economics spectrum describes biome‐invariant scaling functions for leaf functional traits that relate to global primary productivity and nutrient cycling. Here, we develop a comprehensive framework for the origin of this leaf economics spectrum based on venation‐mediated economic strategies. We define a standardized set of traits – density, distance and loopiness – that provides a common language for the study of venation. We develop a novel quantitative model that uses these venation traits to model leaf‐level physiology, and show that selection to optimize the venation network predicts the mean global trait–trait scaling relationships across 2548 species. Furthermore, using empirical venation data for 25 plant species, we test our model by predicting four key leaf functional traits related to leaf economics: net carbon assimilation rate, life span, leaf mass per area ratio and nitrogen content. Together, these results indicate that selection on venation geometry is a fundamental basis for understanding the diversity of leaf form and function, and the carbon balance of leaves. The model and associated predictions have broad implications for integrating venation network geometry with pattern and process in ecophysiology, ecology and palaeobotany.

Status of the long-tailed macaque Macaca fascicularis in Singapore and implications for management - John Chih Mun Sha; Michael D. Gumert; Benjamin P. Y.-H. Lee; Agustin Fuentes; Subaraj Rajathurai; Sharon Chan; Lisa Jones-Engel (Biodiversity and Conservation, 2009)

BRMS1 suppresses breast cancer metastasis in multiple experimental models of metastasis by reducing solitary cell survival and inhibiting growth initiation - Benjamin D. Hedley; Kedar S. Vaidya; Pushar Phadke; Lisa MacKenzie; David W. Dales; Carl O. Postenka; Ian C. MacDonald; Ann F. Chambers (Clinical & Experimental Metastasis, 2008)

Major differences observed in transcript profiles of blueberry during cold acclimation under field and cold room conditions - Anik L. Dhanaraj; Nadim W. Alkharouf; Hunter S. Beard; Imed B. Chouikha; Benjamin F. Matthews; Hui Wei; Rajeev Arora; Lisa J. Rowland (Planta, 2007)

Ecological response to hurricane events in the Pamlico Sound system, North Carolina, and implications for assessment and management in a regime of increased frequency - Hans W. Paerl; Lexia M. Valdes; Alan R. Joyner; Benjamin L. Peierls; Michael F. Piehler; Stanley R. Riggs; Robert R. Christian; Lisa A. Eby; Larry B. Crowder; Joseph S. Ramus; Erika J. Clesceri; Christopher P. Buzzelli; et al. (Estuaries and Coasts, 2006)

Gender-influenced obesity QTLs identified in a cross involving the KK type II diabetes-prone mouse strain - Benjamin A. Taylor; Lisa M. Tarantino; Sandra J. Phillips (Mammalian Genome, 1999)

Genetic variation in alkaline phosphatase of the house mouse (Mus musculus) with emphasis on a manganese-requiring isozyme - Frank H. Wilcox; Lisa Hirschhorn; Benjamin A. Taylor; James E. Womack; Thomas H. Roderick (Biochemical Genetics, 1979)